What Is a Barrier to Entry? - McAfee, R. Preston; Mialon, Hugo M; Williams, Michael A (American Economic Review, 2004)
The present article is an attempt to resolve the controversies concerning the concept of barriers to entry. We begin by contrasting the definitions of an entry barrier proposed in the economics literature. We then introduce a classification system to clear up the existing confusion, and we employ it to assess the nature of the barriers posed by scale economies and sunk costs.